In Vitro Germination And Development Of Aeschynomene Indica L. - P.L.INDIRA,; S. SIVA SUBRAMANIAN,; JUNIOR DYAKU,; M. ANITHA,; R.KARTHIKADEVI,; P. POTHAMMAL,; D. SURESH,; A. RENUKA,; R.BALAMANI,; V.ARULMATHI,; R.KANIMOZHI, (International Journal of Pharma and Bio Sciences, 2012)
A procedure for in vitro culture of the economic important plant Aeschynomene indica L. is described. A factorial experiment evaluated the effects of media Murashige and Skoog’s medium (MS) and Gamberg et al., (B5 ) medium, temperatures (15° C and 20° C) presence or absence of light and plant growth regulators. Seed explants germinated in less than one week in culture and produced radicles. Optimal conditions for radical elongation were B5 at 20° C in the presence of light and without plant growth regulators. Plants were elongated on the same medium without plant growth regulators and acclimation to green house conditions.